Reduction of ISI using CLS-DFE technique for STF MIMO-OFDMA system / Siti Maisurah Sulong - Sulong, Siti Maisurah (2014)
Orthogonal frequency division multiple access (OFDMA) is one of the modulation technique designed to have high speed data rate transmission in wireless communication system. Inter symbol inteference (ISI) is a main cause that can reduce efficiency of the system due to multipath propagation.